Internalisasi Nilai-Nilai Moderasi Beragama melalui Mata Pelajaran Pendidikan Pancasila pada Peserta Didik di SDN 238 Palembang: Penelitian - Riska Amalia; Midya Botty; Yunita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study investigates the internalization of religious moderation values through Pancasila Education among students at SDN 238 Palembang. The research aims to analyze the process, supporting and inhibiting factors, and the effectiveness of value internalization in the classroom. Employing a qualitative case study approach, the research involved all students of class I C, the Pancasila Education teacher, and the principal as key informants. Data were collected using interviews, observation, and documentation, with analysis conducted through Miles and Huberman’s interactive model. The findings reveal that the internalization process occurs in three stages: value transformation, value transaction, and value transinternalization. Supporting factors include adequate facilities, a conducive school environment, active family involvement, teacher facilitation, and student engagement. Inhibiting factors are limited student comprehension, external environmental influences, uncontrolled social media use, and low literacy culture. The study concludes that effective collaboration between school, family, and community is essential for fostering moderate character in students.